Gangs on Trial: Challenging Stereotypes and Demonization in the Courts - Hagedorn, John (Studies in Transgression Ser., 2022)
Intro -- Contents -- Foreword by Craig Haney -- Acknowledgments -- A Note on Names -- Introduction -- Part I. Stereotypes and Frames -- 1. The Nature of Gang Stereotypes: What Is a "Gang-Related" Crime? -- 2. "Increasing Status in the Gang": Fast Thinking and Overcharging in Gang-Related Crimes -- 3. Is This a Just World? How Stereotypes and Beliefs Change-A Personal Story -- 4. Frames and Facts: Contesting the Gang Frame -- 5. Cracks in the Frame: Subtyping and Stereotypes-A Personal Story -- 6. Crooked Frames: Giving Stereotypes a Boost -- Part II. Dehumanization -- 7. There Is No Such Thing as a Gang Member: Priming, Prototypes, and the Subconscious -- 8. Course Correction: Police, Racism, and China-A Personal Story -- 9. "Us" and "Them": Racism and the Psychological Basis for Mass Incarceration -- 10. "I Did What You Said I Did. But I'm Not Who You Say I Am.": Jacqueline Montañez and the Fundamental Attribution Error -- Part III. The Struggle for Justice: Reframing Stereotypes and Overcoming Demonization -- 11. Don't Start Acting Human on Me Now: Prosecutors, Police, and Jail-A Personal Story -- 12. I Am Not a Hired Gun: Reframing and the Expert Witness Role -- 13. Humanizing Justice -- Epilogue to the Stories -- References -- Index.